1997
DOI: 10.1093/toxsci/36.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifetime Lead Exposure in Monkeys on Detection of Pure Tones

Abstract: Increased detection thresholds for pure tones were observed in a large cohort of children exposed to lead environmentally while smaller studies in lead-exposed workers have reported conflicting results on assessments of auditory function. Pure tone detection thresholds were determined in a group of monkeys (Macaco fascicularis) dosed with 2 mg/kg/day of lead from birth through testing at 13 years of age. Blood lead concentrations were stable at about 30 /ig/dl until monkeys were 10-11 years of age, at which ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
1
3
0
1
Order By: Relevance
“…In this same study, prolonged latencies of ABR waveforms were also seen in those children with the highest lead levels [Osman et al, 1999]. A report on chronically lead-exposed monkeys also revealed elevated PTTs in roughly half of exposed animals compared to control animals [Rice, 1997]. Furthermore, DPOAE responses in these monkeys revealed significantly reduced emissions in 20% of exposed animals [Lasky et al, 1995].…”
Section: Leadsupporting
confidence: 59%
“…In this same study, prolonged latencies of ABR waveforms were also seen in those children with the highest lead levels [Osman et al, 1999]. A report on chronically lead-exposed monkeys also revealed elevated PTTs in roughly half of exposed animals compared to control animals [Rice, 1997]. Furthermore, DPOAE responses in these monkeys revealed significantly reduced emissions in 20% of exposed animals [Lasky et al, 1995].…”
Section: Leadsupporting
confidence: 59%
“…Essa constatação foi apresentada por Rice 16 em seus estudos com cobaias, nos quais observou que os limiares elevados apresentaram padrões desordenados de respostas, bem diferentes daqueles encontrados nas patologias cocleares causadas por agentes que danificam as células ciliadas externas do Órgão de Corti.…”
Section: Introductionunclassified
“…For example, among the 6-19 year olds evaluated in the Hispanic Health and Nutrition Examination Survey, an increase in blood lead level from 7 to 18 mg/dl was associated with approximately a 2 dB hearing loss at all frequencies tested (500, 1,000, 2,000, 4,000 Hz) in children (Schwartz & Otto, 1991, p. 303). Elevated thresholds for pure tones, particularly at higher frequencies, were also reported for a group of 13-year-old monkeys (M. fascicularis) that had been exposed to lead daily since birth (Rice, 1997).…”
Section: Discussionmentioning
confidence: 67%
“…The contribution to these effects of current versus previous blood lead level could not be addressed directly in these studies, but was addressed indirectly by Robinson et al Results suggested the effects were due primarily to current blood lead levels. Elevated thresholds for pure tones, particularly at higher frequencies, were also reported among a group of 13-year-old lead-exposed monkeys (Macaca fascicularis) (Rice, 1997). However, exposure for those monkeys was continuous from birth to the time of testing.…”
Section: Studies In Rhesus Monkeysmentioning
confidence: 84%